2008
DOI: 10.33899/mmed.2008.32311
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue sarcomas in Mosul: a pathologic evaluation

Abstract: Objective: Histochemical and immunohistochemical examination of soft tissue sarcomas(STS) in Mosul to assess the value of these techniques in verifying the primary diagnosis. Methods: Paraffin embedded tissue blocks of 35 cases of soft tissue sarcomas collected over a period of 20 months in Mosul, were utilized. H&E, reticulin ,and Van Gieson's staining techniques and immunohistochemical marker for S-100 protein were applied to all the cases. Results: Soft tissue sarcoma accounts for 16.4%of the total of 213 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However different results in study done by Lazim et al [19] . Pramila Jain et al reported that 40% of soft tissue tumorsoccursin lower extremities [7] .…”
Section: Discussionmentioning
confidence: 80%
“…However different results in study done by Lazim et al [19] . Pramila Jain et al reported that 40% of soft tissue tumorsoccursin lower extremities [7] .…”
Section: Discussionmentioning
confidence: 80%